TENDENCIES IN COPS PRODUCTION DEVELOPMENT IN REPUBLIC OF SRPSKA - Nedeljković, Miroslav (ACADEMIC REVIEW, 2018)
Cereal production forms the basis of plant production in the Republic of Srpska, and therefore it is necessary to pay particular attention to the tendency of development of its basic producers, such as areas, production and yields. The author uses quantitative methods of research to analyze the movement of the basic production characteristics of selected cereals in the Republic of Srpska in two ten-year subperiods, with the aim of pointing to their developed tendencies. The results show that there has been a fall in the area under the grain of the last eleven years from about 1%, and that the highest average areas, production and yield are represented in corn. High instability of production trends is present in all observed cereals in both measured subperiods, while the highest average yield is recorded in maize, with the greatest instability in the yield trend and in one and the other period.